Urban Conflict Vs. Urban “War:” Another “Key” to Read the Conflict in Medellin - Blair, Elsa; Universidad de Antioquia (Editorial Pontificia Universidad Javeriana, 2009)
The urban conflict in Medellin between 1995 and 2002 has been described, fundamentally, as an urban war that can be explained based on the armed political conflict that took place on a national level. The presence of armed actors linked to the Autodefensas Unidas de Colombia(AUC) – essentially the "cacique nutibara" block – and the guerilla groups Fuerzas Armadas Revolucionarias de Colombia FARC and Ejercito de Liberacion Nacional ELN, allowed many analysts to explain the conflict in Medellin as a "local expression" of the conflict that took place on the national stage. This article questions this thesis. Instead it suggests that more than an urban "war," explainable from the national situation and under a conception of state and instrumental/rational politics and power, Medellin has been living inserted into a multiplicity of conflicts that articulate in specific ways, and which involve much more subjective aspects that can be seen in pre-existing neighborhood dynamics from before the "war," which because of these circumstances we prefer to call urban conflict instead. On the basis on what we found during the investigation and centered on systematic and extensive fieldwork (workshops, interviews, walkthroughs, images, photographs etc.) that took four months to complete, we suggest to the experts on urban violence some new "keys" to interpret the conflict in Medellin. One of those is tied to subjective aspects or dimensions of neighborhood life that intervene significantly in conflict dynamics, including political conflicts